The Influence of Human Resources Competency on Employees Performance - Kiki Aprilia; Nur Zeina Maya Sari; Dedy Sudarmadi (Almana : Jurnal Manajemen dan Bisnis, 2020)
This study aims to determine how much the Human Resources Competency on Employee Performance Studies at Retail Planet Fashion Bandung. In this study, the dependent variable is employee performance and the independent variable is human resource competency. The method used in this research is descriptive, quantitative, verification method, while the method of data collection done by distributing questionnaires and using sampling methods, namely the purposive sampling method in processing the samples used. The results of this study indicate that there is an influence of the competency of resources on employee performance.